Model Pembelajaran Snowball Throwing Terhadap Peningkatan Hasil Belajar Siswa Mata Pelajaran Pendidikan Agama Islam Kelas VIII SMP - Layyinnati, Idzi; Agustina, Susi milad (STIT Muhammadiyah Paciran Lamongan, 2023)
The purpose of this study is: To test whether there are differences in student learning outcomes before using the Snowball Throwing model with the learning outcomes of students who have used the Snowball Throwing model. To find out the effect of the Snowball Throwing learning model on improving student learning outcomes in Islamic Religious Education for class VIII at SMP Muhammadiyah 25 Modern Paciran Lamongan. From the results of data analysis it was found that student learning outcomes had increased. In the Pre-Test questions, the average student score was 74.36 with a classical learning mastery of 51%. In the Post-Test questions, the average score of students increased by 84 with classical learning mastery reaching 85%. Thus it can be said that learning using the Snowball Throwing model can improve student learning outcomes in Islamic Religious Education class VIII at SMP Muhammadiyah 25 Modern Paciran Lamongan..